THE RELATIONSHIP BETWEEN ISLAMIC RELIGIOSITY LEVEL AND ADOLESCENT DATING BEHAVIOR - Andayaningtyas, Yunita; Utami, Ratih Dwilestari Puji; Agustin, Wahyu Rima (Universitas Kusuma Husada Surakarta, 2025)
Background: Adolescence is a transitional phase from childhood to adulthood. At this stage, various issues emerge, with dating behaviour being one of the prominent concerns. Dating is a form of socialisation that is influenced by Western culture. Dating behaviour that leads to risky sexual behaviour may generate various health problems, such as unwanted pregnancy, abortion, sexually transmitted infections, dropping out of school for pregnant adolescent girls, exchanging parental roles, ostracism from the community, and decreased quality of life. These negative impacts can be minimised by increasing religiosity. Religiosity recreates a function in influencing and regulating one's behaviour. This study aimed to determine the relationship between Islamic religiosity and adolescent dating behaviour.Methods: This study employed quantitative methods with a correlational design and a cross-sectional approach. The sample consisted of 40 students using a total sampling technique. Data were collected using a questionnaire validated with an R value greater than 0.355, confirming its validity. Bivariate analysis was performed using the Spearman Rho test.Results: The results revealed that most respondents were in early adolescence (12-14 years), comprising 33 students (82.5%), with most being male (25 students or 62.5%). A high level of religiosity was observed in 32 students (80%), and non-risky dating behaviour was reported in 32 students (80%). The Spearman Rank test obtained a p-value = 0.000 (p < 0.05).Conclusions: The study concluded that a significant relationship existed between Islamic religiosity and adolescent dating behaviour at MTs Negeri 1 Sukoharjo.